The effects of electrification on employment in rural Peru - Dasso, Rosamaría; Fernandez, Francisco A. (Springer, 2015)
We study the effects of a rural electrification program on employment in Peru. Taking advantage of the program's roll-out across districts over time, we adopt differences-in-differences and fixed-effects strategies to estimate the impact of electrification on labor market outcomes. Our preferred specification suggests that, among males, the program increases hours of work and diminishes the likelihood of having a second occupation. Among females, the treatment raises employment and earnings and increases the probability of working outside the agricultural sector. JEL codes J22; O13